Pre-breeding energetic management in a mixed-strategy breeder - Hennin, Holly L.; Legagneux, Pierre; Bêty, Joël; Williams, Tony D.; Grant Gilchrist, H.; Baker, Tyne M.; Love, Oliver P. (Oecologia, 2015)
Integrative biologists have long appreciated that the effective acquisition and management of energy prior to breeding should strongly influence fitness-related reproductive decisions (timing of breeding and reproductive investment). However, because of the difficulty in capturing pre-breeding individuals, and the tendency towards abandonment of reproduction after capture, we know little about the underlying mechanisms of these life-history decisions. Over 10 years, we captured free-living, arctic-breeding common eiders (Somateria mollissima) up to 3 weeks before investment in reproduction. We examined and characterized physiological parameters predicted to influence energetic management by sampling baseline plasma glucocorticoids (i.e., corticosterone), very-low-density lipoprotein (VLDL), and vitellogenin (VTG) for their respective roles in mediating energetic balance, rate of condition gain (physiological fattening rate) and reproductive investment. Baseline corticosterone increased significantly from arrival to the initiation of reproductive investment (period of rapid follicular growth; RFG), and showed a positive relationship with body mass, indicating that this hormone may stimulate foraging behaviour to facilitate both fat deposition and investment in egg production. In support of this, we found that VLDL increased throughout the pre-breeding period, peaking as predicted during RFG. Female eiders exhibited unprecedentedly high levels of VTG well before their theoretical RFG period, a potential strategy for pre-emptively depositing available protein stores into follicles while females are simultaneously fattening. This study provides some of the first data examining the temporal dynamics and interaction of the energetic mechanisms thought to be at the heart of individual variation in reproductive decisions and success in many vertebrate species.